Peningkatan Mutu Layanan Sekolah Melalui Digitalisasi Pengumuman Kelulusan di SMP Negeri 1 Kabila Gorontalo - Arip Mulyanto; Hermila A.; Dian Novian; Sitti Suhada; Muthia Muthia (Universitas Negeri Gorontalo, 2026)
This community service project is titled “Improving the Quality of School Services Through the Digitization of Graduation Announcements for Fast and Accurate Access to Information at SMP Negeri 1 Kabila Gorontalo.” This program was implemented in response to the challenges faced by our partner in managing graduation announcement services. Prior to the implementation of this community service activity, the existing system had limitations in providing fast, stable, and integrated information services, which potentially hindered the delivery of information to students. Additionally, the administrative management of graduation announcements was not supported by a centralized system, and the competencies of teachers and administrative staff in operating web-based information systems still needed to be improved. To address these issues, the community service team developed and implemented the SMP Negeri 1 Kabila Graduation Status Check Website, built on the Laravel framework. The website features graduation status checks using the National Student Identification Number (NISN), student data management, bulk data import, scheduling of announcement publication, and an administrator dashboard. The implementation of this technology was supported by outreach activities, training, and mentoring for teachers and administrative staff to enable them to operate and manage the system independently. In addition, the community service team also compiled a user guide for the website as a medium to support the transfer of science and technology (IPTEK). The results of the activities showed that the “Cek Kelulusan” website was successfully implemented as the official medium for announcing graduation results at SMP Negeri 1 Kabila. The developed system has improved the efficiency of administrative management for graduation announcements, facilitated students’ access to information, and enhanced the digital competencies of teachers and administrative staff in operating web-based information systems. The outcomes of the project include the “Cek Kelulusan” website, a user guide for the system, capacity building for partner human resources, and the establishment of partnerships that support the sustainability of the school’s digital transformation. Thus, this community service project has made a tangible contribution to improving the quality of educational services through the effective, efficient, and sustainable use of information technology at SMP Negeri 1 Kabila.